“Bridging the Gap between International Investment Law and the Environment”, 4th and 5th November, The Hague, The Netherlands - Diepeveen, Rosalien; Levashova, Yulia; Lambooy, Tineke (Utrecht Journal of International and European Law, 2014)
This contribution is based on the discussions that took place in the international conference “Bridging the Gap between International Investment Law and the Environment” which was held on 4-5 November 2013 in the Hague. The main goal of the conference was to answer the question of how the gap between international investment law and the environment can be bridged. Different perspectives were presented, helping to shed light on this issue. The emphasis of the first day of the conference was the academic debate in the field of international investment law and the environment. Four main perspectives were discussed: general principles of international investment law and the environment, various legal regimes, specific legal regimes and case studies. Furthermore, also the topics of sustainable development, the right to access to water and climate change were elaborated upon by the experts. The second day of the conference focussed on the perspective of policy-makers. Most of the topics were presented in the form of panel discussions. Issues that were discussed included: the perspective of various intergovernmental organisations, concerns and dilemmas of non-European capital-importing countries, and the European Investment Policy. This contribution elaborates upon the most important themes and issues debated at the conference, providing academic and policy perspectives.